The Influence Of Institutional Ownership And Profitability On Company Value With Dividend Policy As A Moderating Variable - Miles Aritopan; Sri Hermuningsih; Riskin Hidayat (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This research aims to examine the influence of institutional ownership and profitability on company value by considering dividend policy as a moderating variable in banking companies on the Indonesia Stock Exchange for the 2017-2022 period. The research method used is path coefficient analysis to test the relationship between variables. Data was obtained from annual reports of banking companies registered on the IDX. The research results show that there is a positive and significant influence between the profitability variable on company value with a significance value of 0.006 (<0.05) while the institutional ownership variable does not have a positive and insignificant influence with a significance value of 0.309 (>0.05). Apart from that, dividend policy as a moderating variable is able to influence the relationship between profitability and company value with a significance value of 0.000 (<0.05), while dividend policy is not able to influence the relationship between institutional ownership and company value. Thus, the conclusion of this research is that institutional ownership has no effect on company value with or without considering dividend policy, while profitability has a direct and significant influence on company value with or without considering dividend policy. Therefore, company management needs to pay attention to these factors in managing company policies and investments to increase long-term company value.